The Implementation of Grant of Marriage Properties Distribution Through Conciliation Agreement - DANIYANTHI, Yussie Masyuni; SUJANA, I Nyoman; AGUNG, Anak Agung Istri (Indonesia Strategic Sustainability, 2025)
This empirical legal research examines the implementation of grants for the distribution of marital properties through conciliation agreements, focusing on the differences between Balinese customary law and societal practices. The study aims to identify legal issues and contribute ideas to improve the implementation of marital joint property distribution through conciliation agreements. Employing a statutory, case-based, and sociological approach reveals that parties who have undergone a divorce can waive court orders and distribute joint properties through conciliation agreements in accordance with Balinese customary law. In this context, the position of husband and wife in marital property is considered equal. However, the study clarifies that the distribution of joint marital properties through conciliation agreements does not automatically transfer ownership unless the joint property is in the form of land rights. In such cases, a deed of grant prepared by a Land Deed Conveyancer (PPAT) is required to transfer ownership to each party and minor children. This process ensures legal certainty in the rights of each party involved. The study highlights the importance of understanding the specific legal requirements for transferring ownership of different types of joint properties. It emphasizes the need for a comprehensive approach to achieving fairness and clarity in marital property distribution through conciliation agreements.